2002
DOI: 10.1590/s1519-69842002000500002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the embryonic development of the annual fish Cynopoecilus melanotaenia (Cyprinodontiformes, Rivulidae)

Abstract: The present study aims to provide data about the time required for Cynopoecilus melanotaenia kept at different temperatures to complete embryonic development. This information can be valuable for optimizing laboratory culture and facilitating future use of this species as a test organism in toxicity tests. Temperature effects on hatching rate are presented as well as information related to embryonic development stages. Eggs were observed daily, from start to finish of embryonic development. Thirteen developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 14 publications
(15 reference statements)
2
33
1
Order By: Relevance
“…Hatching period of M. fluviatilis was between 7 and 9 days, whereas of M. s. splendidia, between 4 and 8 days of embryonic development. Arenzon et al (2002), mentioned that M. s. australis, M. s. inornata and M. niigrans (Melanotaenia genus species), presented embryonic period of 4.5 days at 26°C (Humphrey et al, 2003). Larvae hatched through corium rupture in a very fast way, similar to the observed by Ferreira et al (2009) to the…”
Section: Resultsmentioning
confidence: 99%
“…Hatching period of M. fluviatilis was between 7 and 9 days, whereas of M. s. splendidia, between 4 and 8 days of embryonic development. Arenzon et al (2002), mentioned that M. s. australis, M. s. inornata and M. niigrans (Melanotaenia genus species), presented embryonic period of 4.5 days at 26°C (Humphrey et al, 2003). Larvae hatched through corium rupture in a very fast way, similar to the observed by Ferreira et al (2009) to the…”
Section: Resultsmentioning
confidence: 99%
“…Hisaoka & Firlit (1960) reported that, in zebrafish, the mitotic divisions are synchronous until 32 cells but become asynchronous at 64 cells. Arezon et al (2002) reported that embryos of Cynolebias melanotaenia develop faster at 25…”
Section: Discussionmentioning
confidence: 99%
“…However, the resting eggs remain on diapause, waiting the next rainy season, when they will hatch and start a new life cycle (Podrabsky & Hand 1999). Annual fish have been used as model organisms for laboratory (Arenzon et al 2002a(Arenzon et al , 2003, bioindicators (Arezo et al 2007), pest control (Fletcher et al 1992, Frenkel & Goren 2000 and ornamental fish (Costa 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature has been shown to influence Rivulidae fish in terms of reproduction (Arenzon et al 1999), time of the embryonic development (Arezo et al 2007, Arenzon et al 2002a), growth (Errea & Danulat 2001, Walford & Liu 1965, Liu & Walford 1970, and longevity (Walford & Liu 1965, Liu & Walford 1966, 1970.…”
Section: Introductionmentioning
confidence: 99%